(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Epithelial ovarian cancer is one of the leading causes of mortality among gynecological malignancies. Diagnosis is often delayed because early symptoms are nonspecific and many patients present with advanced-stage disease. Serum biomarkers are widely used in the diagnostic evaluation of adnexal masses. Cancer antigen 125 (CA-125) is the most established biomarker, but its diagnostic value is limited by false-positive elevation in benign conditions and reduced sensitivity in early-stage disease. Human epididymis protein 4 (HE4) and the Risk of Ovarian Malignancy Algorithm (ROMA), which combines HE4, CA-125 and menopausal status, have been introduced to improve diagnostic discrimination. Objective: To systematically evaluate the role of HE4, CA-125 and ROMA score in the diagnosis of epithelial ovarian cancer. Methods: A systematic review was conducted using PRISMA 2020 principles. PubMed, Scopus, Web of Science, Embase and Google Scholar were searched for studies evaluating HE4, CA-125 and ROMA score in women with suspected epithelial ovarian cancer or adnexal masses. Studies reporting sensitivity, specificity, positive predictive value, negative predictive value, area under the curve or sufficient data for diagnostic interpretation were included. Histopathology was considered the reference standard. Study quality was assessed using QUADAS-2. Findings were synthesized narratively with pooled descriptive estimates. Results: A total of 721 records were identified. After removing 164 duplicates, 557 records were screened. Eighty-six full-text articles were assessed, and 34 studies involving 9,486 women were included. Of these, 2,918 women had epithelial ovarian cancer and 6,568 had benign ovarian or gynecological conditions. Overall, CA-125 showed pooled sensitivity of 82.6%, specificity of 73.8% and AUC of 0.84. HE4 showed sensitivity of 78.4%, specificity of 89.1% and AUC of 0.90. ROMA score showed the best overall diagnostic balance, with sensitivity of 87.5%, specificity of 85.3% and AUC of 0.93. In premenopausal women, HE4 demonstrated higher specificity than CA-125, while ROMA showed stronger balanced performance in postmenopausal women. Conclusion: HE4 and ROMA score improve diagnostic accuracy in epithelial ovarian cancer compared with CA-125 alone. CA-125 remains useful as a sensitive marker, but HE4 provides superior specificity, particularly in benign gynecological conditions. ROMA score offers the best overall risk stratification by integrating biomarker values with menopausal status. These markers should be used as complementary diagnostic tools along with clinical examination, imaging and histopathological confirmation.